Percepções da Enfermagem: um olhar sobre os regimes trabalhistas do Hospital Universitário Federal - Costa, Maristela de Oliveira (2019)
Introduction: federal university hospitals play an important role in society, meet demands of medium and high complexity, make up the Unified Health System network, train and qualify health professionals. In 2011, the Brazilian Hospital Services Company w